CyberScape: A 2D roguelike platformer with procedurally generated levels - Guerreiro, D.; Pereira, F.; Almeida, F.; Alexandre, I.; Lopes, P. F. (Videojogos 2019: 11th International Conference on Videogames Sciences and Arts, 2019)
This paper explores the development of CyberScape, a videogame developed within the scope of four courses of a Master degree program. In this paper, we try to demonstrate that it is possible for a small team during a small peri-od of time to develop a game addressing Procedural Content Generation techniques used for level generation, and finite state machines used for the Non Player Characters control – namely the companion, enemies and bosses. It is also presented the decisions made regarding game design, graphics and sounds. We will also address and discuss the results of user tests that were carried out during several stages of the game’s development.